A Study of Neonatal Near-misses and the Contributing Factors among Neonates Born in Public Hospitals in Addis Ababa, Ethiopia: A Retrospective Cross-sectional - Banchialem Legamo; Endalew Sendo (Iranian Journal of Neonatology, 2023)
Background: Neonatal mortality remains one of the most pressing concerns in the world despite enormous improvements in neonatal intensive care. Although there is a decline in neonatal death in Ethiopia, it is still a major problem. In this study, the prevalence and contributing factors of neonatal near-misses were investigated in neonates admitted to sampling public hospitals in Addis Ababa, Ethiopia.Methods: A facility-based retrospective cross-sectional study of 367 participants was conducted. An interviewer-administered, pre-tested structured questionnaire developed from pertinent literature was used to collect data on mothers by phone. The secondary data were gathered from the mothers' and the newborn's medical records using a pre-tested standardized checklist. An adjusted odds ratio (AOR) with a 95% confidence interval (CI) was computed to determine the level of significance.Results: Neonatal Near Miss [NNM] prevalence was 25.6% (95% CI 21.0-30.5). The NNM was associated with the mother's work (AOR: 0.123, 95% CI: 0.018-0.859), as well as previous preterm deliveries (AOR: 11.83, 95% CI: 1.856- 75.398), Cesarean section (2.39 AOR, 95% CI: 1.229-4.652), pregnancy-related hypertension (2.67, 95% CI: 1.343-5.324), and infection (AOR (AOR 8.925, 95 % CI 2.580 - 30.873). More than half of newborns [51.0 %] were male. In terms of newborn presentation, 91.8 % of newborns had a cephalic presentation, while Breech presentation accounted for 6.9 %. Twenty-seven [7.4%] of the research participants had birth injuries, and 74% suffered from subglacial hemorrhages.Conclusion: Most of the near-miss variables that can be altered or prevented are obstetric, medical, and neonatal-related. Early detection and treatment of the problems may help to improve neonatal outcomes. The Ethiopian government should pay greater attention to the health sector to expand prenatal care visits. Further prospective research is also required to look into additional reasons for newborn mortality.